Fleirgenerasjonsordbøker og tida - Vikør, Lars S. (Nordiske Studier i Leksikografi, 1997)
"Fleirgenerasjonsordbøker" is a Norwegian coinage covering the large-scale dictionary projects which span the time of several generations, like the Oxford English Dictionary, the Dictionary of the Swedish Academy et.al. The article discusses the problems facing such projects in an age ofrapid technological and social change, based on the experiences and present situation of Norsk Ordbok 'Norwegian Dictionary', which covers the Norwegian dialects and the Nynorsk written variety ofNorwegian. Six dilemmas are explored: l) Effectivity vs. quality; 2) Representativity vs. completeness; 3) A wide spectrum of information types vs. concentration on definitions and functional aspects; 4) Uniformity over time vs. adaptation to changing conditions and requirements; 5) The scientific vs. the communicative aspect; 6) (only briefly mentioned) Paper vs. electronics.